Long term results of Endoscopic Lumbar Discectomy using Side viewing Conical working tube - Mohammad Kaif (Romanian Neurosurgery, 2018)
Object: Endoscopic discectomy is a common procure performed worldwide with various devices being used and studies have reported their long term results. In this study we present the long term results of the unique device with separate side viewing channel. Methods: 66 patients of lumbar disc herniation treated between March 2009 to April 2012 using the unique conical working tube with separate side viewing endoscopic channel. Their preoperative and postoperative Oswestry Disability Index (ODI) and Macnab scores were used to evaluate the outcome after a minimum follow of 5 years with mean follow up of 76.18 months. Results: There were 46 males and 20 females with age ranging from19-72 (mean-38.4 years). The follow up ranged from 61 months to 95 months with mean of 76.18 months. The mean preoperative ODI score was 74.7 which decreased to a mean of 7.8 and the outcome evaluated by Macnab criteria was 69.69% excellent, 17 % good, 10% fair, 3.03% poor. 2 patients underwent second surgery. None of the patient had to change their occupation due to their lumbar disc disease. Complications occurred were dural tear in 2 patients, transient foot paresis in 1 patient and 1 discitis in 1 patient which improved on medical management. Conclusion: Endoscopic discectomy using thins Conical working tube is a safe and effective technique for lumbar disc prolapse. It has the advantage for early mobilization, short hospital stay and low cost. The long term results are comparable to the conventional techniques.